Dynamics of income rank volatility: Evidence from Germany and the US - Louis Chauvel; Anne Hartung; Flaviana Palmisano (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
This paper presents a methodology for comparing income rank volatility profiles over time and across distributions. While most of the existing measures are affected by changes in marginal distributions, this paper proposes a framework that is based on individuals' relative positions in the distribution, and is neutral in relation to structural changes that occur in the economy. Applying this approach to investigate rank volatility in Germany and the US over three decades, we show that while poorer individuals within both countries are the most volatile, the volatility trend for the middle class in each of these countries differs.
Keywords: D31; J6; I30; 330; rank volatility; income; risk; inequality; middle class; Germany; US